(untitled) (Pharmacognosy Reviews)
About Phcog.NetNatural products are the most consistent and successful source of drugs. In India, Ayurveda remains one of the most ancient and living traditions, which is practiced for the treatment of various diseases and disorders. India has many number of plant species and medicinal properties have been assigned to several thousands. Many major institutes and research centres are currently involved in exploring this opportunity to investigate newer drugs from ancient principles of ayurveda. Further researchers believe in combining the strengths of ayurveda with modern scientific techniques such as NMR, MS and chromatographic techniques to provide new functional leads with high therapeutic value in a short span of time. But Natural products research often comes across many hurdles, which dims the drug development goals. We believe that natural products research information can potentially benefit many researchers involved in this area. Also we believe that the research on natural products is often staggered due to lack of required information available for medicinal plants. In order to combat these problems, Pharmacognosy Network Worldwide (Phcog.net)- A Platform for Natural Product Researchers was started, which makes innovative use of best tools for information dissemination and solve the hurdles in Natural Product Research. Pharmacognosy Network Worldwide is a non-profit network dedicated to Natural Products Research in order to develop promising drugs.